(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2010)
The red or black colours used to differ between individual days in many calendars are an important aid to organising life in a particular society. The typographical devices used to distinguish days of special importance are instrumental in turning historical events and persons into the images of the nation, which its members can admire, from which they can learn, and–not least–for which they can also fight. The prevailing ideology has a decisive role in the choice of colour for particular days. By defining which days should be marked as particularly important, those in power not only define which days are suitable for work and which for rest. They also appropriate the past, and canonise knowledge and meaning of the past. Radical changes in political systems as a rule bring about changes in the symbolic system of a certain society. Old symbols are withdrawing in order to make way the new ones which represent the new ideology and the new political leadership. In my treatise, I will analyse interventions in the symbolic world on the examples of two holidays, introduced in the Republic of Slovenia in 1992, namely Reformation Day and Day of Remembrance of the Dead. If the first holiday, which has its roots in the Protestant religious tradition, represents a novelty in the Slovenian calendar, has the second – rooted in the Catholic tradition – longer and harder roots. In the analysis of the narrative image of the past, I draw on the model proposed by Marea Teski and Jacob Climo (The Labyrinth of Memory. Ethnographic Journeys, 1995) for constructing and reconstructing the past through the memory repertoire, and applied by Cheryl Natzmer (2002: 164) to her analysis of creative expressions and reconciliation in postPinochet Chile.